Protocol and Statistical Analysis Plan for a Comparative Interrupted Time Series Evaluation of the Impact of Deemed Consent for Organ Donation Legislative Reform in Nova Scotia, Canada - Matthew J. Weiss, MD; Kristina Krmpotic, MD; Stephen Beed, MD; Sonny Dhanani, MD; Jade Dirk, BSc; David Hartell, MA; Cynthia Isenor, RN, MScN; Nick Lahaie; Scott T. Leatherdale, PhD; Kara Matheson, MSc; Karthik Tennankore, MD, SM; Gail Tomblin-Murphy, PhD, BN, MN; et al. (Transplantation Direct)
The Canadian province of Nova Scotia recently became the first North American jurisdiction to implement deemed consent for deceased organ donation as part of a comprehensive legislative reform of their donation and transplantation system. This study will examine the performance metrics and effectiveness of this policy in comparison with other Canadian provinces via a natural experiment evaluation. We will use a cross-sectional controlled interrupted time series quasi-experimental design. Our primary outcome will be consent for deceased donation as confirmed at the time of eligibility (prior registered intent to donate will be noted but not be considered positive unless affirmed at the time of eligibility). Secondary outcomes will include identification and referral of patients who are potential donors, rates of family override of previously registered intent to donate, and donation and transplantation rates per million population. Data will be collected from potential donor audits in Nova Scotia and 3 control provinces (provinces in Canada without deemed consent policies). Study outcomes will be compared in Nova Scotia relative to control provinces in the 3 y before and 3 y after the implementation of legislative reform. These provinces were selected as having systems resembling those of Nova Scotia but without deemed consent.Using controlled interrupted time series methodology compared with other Canadian provinces with otherwise similar systems, we aim to isolate the impact of the deemed consent aspect of legislative reform in Nova Scotia using a robust natural experiment evaluation design as much as possible. Careful selection of outcome measures will allow donation and transplantation stakeholders to properly evaluate if similar reforms should be considered in their jurisdictions.